Greater glycosaminoglycan content in human patellar tendon biopsies is associated with more pain and a lower VISA score. Issue 6 (6th October 2013) - Attia, Mohamed; Scott, Alexander; Carpentier, Gilles; Lian, Øystein; Van Kuppevelt, Toin; Gossard, Camille; Papy-Garcia, Dulce; Tassoni, Marie-Claude; Martelly, Isabelle
Abstract : Background: People with patellar tendinopathy experience chronic pain and activity limitation, but a pertinent biochemical marker correlated with these clinical features has not been identified. The Victoria Institute of Sport Assessment (VISA) questionnaire is a condition-specific patient-rated outcome measure. Since the quantity of glycosaminoglycans (GAGs) increases with advancing tendon pathology, we hypothesised that there would be a correlation between the quantity of GAGs in the patellar tendon and the VISA score. Methods: Tissue biopsies from athletes with chronic patellar tendinopathy (confirmed by clinical examination and MRI) were recruited (n=7), as well as controls with no history of knee pain (n=4). The quantity of sulphated GAGs in the human patellar tendons was determined with a dimethyl methylene blue (DMMB) assay; this method was first validated with rat tendon tissue. The extent and distribution of GAG species and proteoglycans (decorin, versican and aggrecan) in the human tendon biopsies were examined using immunohistochemistry. Results: Greater sulphated GAG content of the patellar tendon was correlated with the greater tendon dysfunction (R 2 =0.798). The quantity of aggrecan in the tendon, a chondroitin sulphate-rich proteoglycan, also increased with advancing tendon pathology. Conclusions: Increased GAGs in the pathological human patellar tendon are related to a worse clinical status. These findings indicate that the VISA score reflects the extent of tendon tissue pathology.